PENGARUH LINGKUNGAN FISIK KELAS DAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Murtiasih, Diah (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2015)
The research aims at investigating: (1) whether there is a significant effect on physical classroom environment towards the learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014; (2) whether there is a significant effect on parents? support towards the learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014; (3) whether there is a significant effect on physical classroom environment and parents? support comprehensively towards the learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014.This research?s design is descriptive quantitative. The population of the research is 72 students of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014. The samples which are taken by applying Simple Random sampling technique are 43 students. Questionnaire is used to do the data collecting method, and statistical test with Double Regression Analysis is applied as the data analysis technique.The results of the research are: (1) there is a significant effect on physical classroom environment towards the learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014. It is proved by the result of rcount > rtable or 0.430 > 0.310 on significance value of 5%. The relative contribution is 29.40% and the effective contribution is 6.19%; (2) there is a significant effect on parents? support towards learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014. It is proved by the result of rcount > rtable or 0.430 > 0.310 on significance value of 5%. The relative contribution is 70.60% and the effective contribution is 14.87%; (3) there is a significant effect on physical classroom environment and parents? support comprehensively towards the learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014. It is proved by the result of Fcount > Ftable or 9.794 > 3.23 on significance value of 5%.From the result of the statistical count, it is known that the linear regression ? = 27.998 + 0.344 X1 + 0.319 X2 which means the learning motivation (Y) will increase or decrease as much as 0.344 for each increase or decrease of a unit of class physical environment (X1) and also will increase or decrease as much as 0.319 for each increase of decrease of a unit of parents? support (X2). Keywords: class physical environment, parents? support, learning motivation